Proceedings of the 3rd Annual International Seminar on Transformative Education and Educational Leadership (AISTEEL 2018) 2018
DOI: 10.2991/aisteel-18.2018.123
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Language Style with Reference to Sex Differences in Teaching English

Abstract: The Objectives of this paper were to describe the types of language styles used by male and female teachers in teaching English in the classroom and the reasons of the using those language styles by the teachers. The subjects were the teachers of SMP Negeri Pancurbatu, they were four English teachers, consits of two male teachers and two female teachers. It was qualitative explanative research designs. The researcher observed the teachers while teaching in order to get the teachers language styles taking place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…It is in line with the finding of the current study that female teachers tended to give positive reinforcement through compliment compared to male teachers more frequently. Nelson's study in (Sinaga & Husein, 2018) also showed a similar finding that students believe that their female teachers are more sensitive and consider more their ideas compared to their male teachers. Besides that, Furumo & Pearson (2007) stated that the communication patterns of men and women are different.…”
Section: The Difference Between Male and Female Teachers In Giving Rementioning
confidence: 66%
“…It is in line with the finding of the current study that female teachers tended to give positive reinforcement through compliment compared to male teachers more frequently. Nelson's study in (Sinaga & Husein, 2018) also showed a similar finding that students believe that their female teachers are more sensitive and consider more their ideas compared to their male teachers. Besides that, Furumo & Pearson (2007) stated that the communication patterns of men and women are different.…”
Section: The Difference Between Male and Female Teachers In Giving Rementioning
confidence: 66%
“…Studies on language styles of both spoken and written language have also been conducted by several researchers. Sinaga & Husein (2018) analyses the language styles used by male and female teachers in teaching English in a classroom. They found that male and female teachers mostly used formal style.…”
Section: B Interjections and Hesitation Fillersmentioning
confidence: 99%
“…While Sinaga & Husein (2018) look at the use of certain language style on the teacher side, Amiri & Puteh (2017) and Mohammed & Abdalhussein (2015) concern on the formal writing style of students' texts emphasising on the errors made by Iranian and Iraqi postgraduate students. Meanwhile, this research was conducted to fill the gap by focusing on the style of academic argumentative essays written by undergraduate Indonesian students.…”
Section: B Interjections and Hesitation Fillersmentioning
confidence: 99%
“…According to Situmorang and Herman (2021), a method to see someone's personality and soul can be shown from a language style. There are four types of language styles: formal, informal, colloquial, and slang (Kirszner & Mandel, 2003, as cited in Sinaga, Sumarsih, & Husein, 2018). The fourth category, slang, will be explored in this study.…”
Section: Introductionmentioning
confidence: 99%